Voices of Challenge in Australia’s Migrant and Minority Press
XIX, 293 p. 7 illus.
Keywords: “Dewhirst and Scully once more bring together a thought-provoking compilation of original studies of Australia’s minority and migrant press. The thematic scope and chronological range are wide. There is much to be learned and pondered in this well-edited volume.” — Cameron Hazlehurst, Australian National University “The authors show how diverse groups used print culture to strengthen their communities and challenge those in power. In the spirit of ‘history from below’ these essays demonstrate that a focus on marginalised groups can cast light on wider national, diasporic and world histories.” — Ann Curthoys AM, University of Sydney, Australia “The fascinating essays compellingly restore unjustly neglected communities and visions to their rightful place. They provide a valuable new perspective on Australian history and an important contribution to global and alternative journalism studies.” — Mark Hampton, LingnanUniversity, Hong Kong This book brings together long-obscured histories to discuss Australia’s cultural, social, and political diversity in depth. The history of Australia’s migrant and minority print media reveals extensive evidence for the nation’s global connectedness, from the colonial era to today. A fascinating and complex picture of Australia’s long-term transnational ties emerges from the smaller enterprises of individuals and communities in the distant and more recent past. This book explores the authentic voices of minority groups which challenged the dominant experiences, patterns, and debates that have shaped Australia. Catherine Dewhirst is Senior Lecturer in History at the University of Southern Queensland, Australia. She has published on Italian-migrant histories and coedited, with Richard Scully, The Transnational Voices in Australia’s Migrant and Minority Press (Palgrave, 2020). Richard Scully is Associate Professor in Modern History at the University of New England, Australia. He is the author of numerous studies of the history of cartoons and caricature, including Eminent Victorian Cartoonists (3 volumes, 2018) and British Images of Germany (Palgrave, 2012).